2009
DOI: 10.4141/cjss08006
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient uptake of hybrid poplar in competition with weeds using the soil supply and nutrient demand (SSAND) model

Abstract: . 2009. Nutrient uptake of hybrid poplar in competition with weeds using the soil supply and nutrient demand (SSAND) model. Can. J. Soil Sci. 89: 197Á207. Mechanistic nutrient uptake models can help gain a quantitative understanding of nutrient uptake by plants under weed-competing conditions. The objectives of this study were to check the applicability of the soil supply and nutrient demand (SSAND) model to predict N, P and K uptake by hybrid poplar (Populus deltoides )Populus)petrowskyana var. Walker) grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Therefore, these results are encouraging given the existing variability in the field, although the model only worked for hybrid poplar N predictions under a single plant species scenario. On the other side, under a two plant species scenario, N uptake predictions were greatly underestimated by both hybrid poplar and weed species and similar results were observed under controlled growth chamber conditions (Kabba et al, 2009). This suggests that many interactive processes occurring at the ecosystem level, particularly under a weed competing environment, may affect the supply of N in the soil and N uptake at the root surface.…”
Section: N Uptake Predictions Under Weed Competition Conditionssupporting
confidence: 58%
See 1 more Smart Citation
“…Therefore, these results are encouraging given the existing variability in the field, although the model only worked for hybrid poplar N predictions under a single plant species scenario. On the other side, under a two plant species scenario, N uptake predictions were greatly underestimated by both hybrid poplar and weed species and similar results were observed under controlled growth chamber conditions (Kabba et al, 2009). This suggests that many interactive processes occurring at the ecosystem level, particularly under a weed competing environment, may affect the supply of N in the soil and N uptake at the root surface.…”
Section: N Uptake Predictions Under Weed Competition Conditionssupporting
confidence: 58%
“…Kabba et al (2009) observed underestimation of N uptake by hybrid poplar under controlled condition for a one plant species' scenario and the underestimation was improved after incorporating N mineralization; however, predictions for the field matched up to the observed N uptake only for the pasture soil and still underestimated N uptake for the alfalfa soil. Therefore, these results are encouraging given the existing variability in the field, although the model only worked for hybrid poplar N predictions under a single plant species scenario.…”
Section: N Uptake Predictions Under Weed Competition Conditionsmentioning
confidence: 44%
“…In perennial plant species, in spite of the evidence for changes in root physiological properties (Escamilla and Comerford 2000; Kelly et al 2001), most studies used similar models as those developed for annual plants to simulate nutrient acquisition (Cropper and Comerford 2005;Gregory 2006;Kabba et al 2009;Kelly et al 1992;Lin and Kelly 2010). To satisfy the hypothesis of stability of plant physiological properties, most of these works on perennial plant species were conducted in controlled conditions, i.e.…”
Section: Root Segment Modelmentioning
confidence: 98%
“…The impact of MSP on soil fertility is more variable, sometimes improving nutrient mobilization (Ross and Malcolm, 1982) and on other occasions reducing it (Messier et al, 1995;Yildiz et al, 2010), notably due to soil organic matter removal (Arocena, 2000;GartziaBengoetxea et al, 2009). Given that hybrid poplars have high needs for resources, they are also known to be particularly sensitive to competition (Stanturf et al, 2001;Kabba et al, 2007Kabba et al, , 2009. Competition control generally has positive effects on early development of seedlings because the first few years are the most critical for survival (Morris et al, 1993;Löf, 2000;Harrington, 2006).…”
Section: Introductionmentioning
confidence: 99%